Konsep Psikologis Tentang Tahap Perkembangan Anak sebagai Landasan Pendidikan Islam - Ghina Fairuz Salsabila; Nuril Huda (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The main problem in this study lies in the lack of a deep and comprehensive understanding of child development from the perspective of Islamic psychology, especially in the context of education. In fact, understanding the stages of child development is very important to design appropriate educational approaches holistically. This study aims to explain the definition of child development psychology, identify psychological concepts in Islamic teachings that are relevant to child growth, and analyze how the principles of Islamic psychology can be applied in child education. The method used is library research with a descriptive-analytical approach, which examines various literatures from modern psychology and classical Islamic sources. The results show that Islam provides a strong conceptual foundation in understanding child development, which includes a balance between intellectual, emotional, spiritual, and moral aspects. Educational psychology in Islam also emphasizes the importance of the active role of parents, teachers, and the surrounding environment in shaping children's character and personality. Thus, the integration between modern psychological theories and Islamic values can be a strategic foothold in developing a child education system that is not only academic, but also oriented towards the formation of noble morals and character.